1996
DOI: 10.1525/maq.1996.10.2.02a00080
|View full text |Cite
|
Sign up to set email alerts
|

Intuition as Authoritative Knowledge in Midwifery and Homebirth

Abstract: As defined by Jordan (1992, 1993[1978]), authoritative knowledge motivates decision and action. Based on interviews with 22 white middle-class midwives in the United States conducted between 1992 and 1993, this article explores the inner knowing that constitutes a primary source of authoritative knowledge for homebirthers but is granted no authority in the realm of technomedicine. The purpose of this article is to call attention to these midwives' utilization of and reliance on intuition as a guide to action a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(88 citation statements)
references
References 26 publications
4
79
0
5
Order By: Relevance
“…The ideal posits women as inherently capable of giving birth without high-tech hospital surveillance (p. 236). Emotional, intuitive, spiritual, narrative, and other ways of knowing (James, 1997, p. 184) are therefore both legitimate and welcome (Cheyney, 2008;Davis-Floyd & Davis, 1996). Brigitte Jordan (1997) contended, however, that biomedical knowledge has become the authoritative knowledge in North American pregnancy care.…”
Section: Discursive Tensions In Midwiferymentioning
confidence: 99%
See 1 more Smart Citation
“…The ideal posits women as inherently capable of giving birth without high-tech hospital surveillance (p. 236). Emotional, intuitive, spiritual, narrative, and other ways of knowing (James, 1997, p. 184) are therefore both legitimate and welcome (Cheyney, 2008;Davis-Floyd & Davis, 1996). Brigitte Jordan (1997) contended, however, that biomedical knowledge has become the authoritative knowledge in North American pregnancy care.…”
Section: Discursive Tensions In Midwiferymentioning
confidence: 99%
“…Brigitte Jordan (1997) contended, however, that biomedical knowledge has become the authoritative knowledge in North American pregnancy care. Jordan and others (see Davis-Floyd & Davis, 1996;Davis-Floyd & Sargent, 1997;Lay, 2000;Spoel, 2004;Stewart, 2001) suggested that biomedical authoritative knowledge underlies a representation of pregnancy as risky, which serves to enhance the authority of physicians over women and over midwives. Annandale (1988) argued that women's expectations of birth are "never fully independent of obstetrical notions of risk" (p. 99).…”
Section: Discursive Tensions In Midwiferymentioning
confidence: 99%
“…Some work in this area has focused on midwives rather than women (Hunter 2002, Rayment 2011 and explored the effects on midwives of working in different settings (Hunter and Deery 2009;Hunter 2003;Ledward 1996;Sandall 1996). Shaw and Kitzinger (2005) and Davis-Floyd and Davis (1996) are among a number of writers who have suggested that women feel more in control of their birth at home or in home-like settings such as free-standing birth centres. One reason given for this feeling of control is that the woman has the higher status of 'resident' at home and the midwife is constructed as a 'visitor', whereas in hospital these roles are reversed (Halford and Leonard 2003).…”
Section: The Literature On Place and Therapeutic Spacesmentioning
confidence: 99%
“…In Ontario, the first province to regulate midwifery as a primary care profession (Ontario Midwifery Act 1991), the College of Midwives (1994Midwives ( /2005 defines informed choice as involving "a co-operative and collaborative information exchange between the midwife and the woman" that supports "the woman as primary decision-maker." Consonant with its roots in the alternative childbirth and women' s health movements of the 1970s, this model explicitly values the exchange of diverse forms of evidence, including emotional, intuitive, spiritual and narrative ways of knowing along with more biomedical and scientific modes (Davis-Floyd and Davis 1996;James 1997;MacDonald 2006).…”
Section: Contextmentioning
confidence: 99%